The Correlation between Estimated Glomerular Filtration Rate and Parathyroid Hormone Levels in Predialysis-chronic Kidney Disease Adult Patients at Sanglah General Hospital, Bali, Indonesia - Herawati, Sianny; Kandarini, Yenny; Prabawa, I Putu Yuda (Open Access Macedonian Journal of Medical Sciences, 2021)
BACKGROUND: Chronic kidney disease (CKD) is a structural or functional kidney disease for more than 3 months. In predialysis CKD patients, the serum parathyroid hormone levels increase progressively since the early stages of the disease to maintain phosphate homeostasis. Glomerular filtration rate (GFR) has been widely accepted to assess renal function. The GFR assessment is used to determine the CKD stadium. AIM: This study aims to analyze the correlation between GFR and parathyroid hormone levels in predialysis CKD patients undergoing treatment at Sanglah General Hospital Denpasar. METHODS: A cross-sectional observational study was conducted among predialysis CKD patients undergoing treatment at Sanglah General Hospital Denpasar who met the inclusion and exclusion criteria. The inclusion criteria were adult patients (≥18 years) who were accepting to participate in the study. Exclusion criteria were patients with predialysis CKD after thyroidectomy and/or parathyroidectomy and liver disease. The parathyroid hormone levels, blood urea nitrogen, creatinine, and GFR were examined and analyzed by SPSS version 17 for Windows. RESULTS: A total of 77 patients with predialysis CKD in this study obtained a median of e-GFR of 21.09 (4.72–75.80) mL/min/1.73 m2. The median level of parathyroid hormone was 82.07 pg/mL (15.83–716.60 pg/mL). Spearman’s correlation analysis results obtained a strong and significant negative correlation between the e-GFR value and parathyroid hormone levels (r = −0.540; p = 0.000). CONCLUSION: The parathyroid hormone levels assessment could be used as a recommendation in evaluating the CKD progressivity among predialysis adult patients at Sanglah General Hospital, Bali, Indonesia, due to the strong significant correlation.